Analisis Kapasitas Parkir Pasar Seni Sukawati Kabupaten Gianyar - Dwi Wahyu Hidayat; Tri Hayatining Pamungkas; Aris Budi Sulistyo (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Sukawati Art Market has 3 Blocks where Blocks A and B were completed in December 2020, and Block C was completed in early 2022. As the number of merchant stalls increases, the number of tourists who come also increases. This affects the parking facilities provided. This study aims to find out the absolute need for parking spaces and the characteristics of the parking at Sukawati Art Market. The method used is a quantitative method where data is obtained by conducting a live survey on Sunday at peak hours, namely from 10:00 to 13:00. The results showed the accumulation of a maximum of 276 vehicles at 11.30-11.45 WITA and 85 vehicles at 12.30-12.45 WITA. The average motorcycle parking turnover rate reached 0.32 vehicles/hour, and cars reached 1.09 vehicles/hour. While the average length of motorcycle parking is 0.82 hours/vehicle, and for Light Vehicles (LV) 1.49 hours/per vehicle. The parking capacity for Motorcycles (MC) reaches 511.98 vehicles/(SRP/hour) while Light Vehicles (LV) reach 34.87 vehicles/(SRP/hour). Provision of Motorcycle (MC) parking spaces amounting to 1382 vehicles and for Light Vehicles (MC) 94 vehicles. The highest parking index for Motorcycles (MC) reached 0.65, which means parking needs are below the available capacity or there are no parking problems, and for Light Vehicles (MC), the highest reaches 1.63, where the capacity is insufficient or parking is experiencing problems. Parking needs are 70.38% for Motorcycles (MC) and for Light Vehicles (LV) by 29.62%.